Pengaruh Return on Asset (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings Per Share (EPS) Terhadap Harga Saham Pada Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2023 - Adawiyah, Robyatul; Prasetya, Bangun Putra (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effect of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings Per Share (EPS) on stock prices in the Agricultural Sector listed on the Indonesia Stock Exchange. Period 2019 - 2023. This study uses a quantitative approach. The population in this study is using Agricultural Sector Companies listed on the Indonesia Stock Exchange (IDX) in the period 2019 - 2023, and by using company financial report data in the agricultural sector. The sample selection technique uses a purposive sampling method. The data analysis method used is multiple linear regression analysis. The results of the study show that Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings Per Share (EPS) together have a significant effect on stock returns. The Adjusted R Square value is 0.571 or 57.1%. This shows that Return On Assets (ROA), Return On Equity (ROE), Debt To Equity Ratio (DER), Earnings Per Share (EPS), have an effect on stock returns of 57.1% while the remaining 42.9% is explained by other variables outside the model.